Integration Model for Utilization of Tilapia Cultivation Waste (Oreocromis niloticus) at the Mangrove Nursery (Rhizopora Sp) For Food Security - Agus Widodo; Yollanda Octavitri; Susiarni Magdalena; Eulis Marlina; Juli Nursandi; Aprilia Syah Putri; Dona Setya (Berkala Perikanan Terubuk, 2023)
The decline in the amount of land and farmers' income can be resolved, one of the ways, is through an integration system between agriculture and fisheries. The integrated system between fish and plants has been proven to have many benefits both ecologically and economically. There has not been much research on the system of integration of fishery farming and cultivation of Tilapia and Mangrove fish on coastal land. Please note that tilapia cultivation is a fishery commodity that is resistant to changes in salinity and also has a relatively high selling price. Research is needed on the integration of fisheries and mangrove plants on coastal land in order to increase the use of land productivity. This research aims to obtain a system integration model between mangrove plants and Tilapia fishery commodities that can increase income for the community. This research was carried out using an experimental method by designing an integrated system for tilapia spawning and mangrove nurseries. The data was analyzed descriptively, studied through comparison of its success with similar fish and mangrove cultivation systems through literature studies. The research results of the designed integration model can be applied in the field. The growth in length and weight of fish is still within the SNI standard range, the survival rate of fish is still below SNI, the growth of mangrove plants and SR of plants is good, the water quality is in accordance with SNI. The advantage of this model is that it can combine fish farming activities and mangrove nursery systems in accordance with government programs in harmonizing economic, ecological and social balance for food security. This integration model is quite feasible to be applied in society